ANATOMICAL PROPERTIES OF NINE INDIGENOUS RATTAN SPECIES OF JAMBI, INDONESIA - Krisdianto Krisdianto; Jasni Jasni; Tutiana Tutiana (Indonesian Journal of Forestry Research, 2018)
Various rattan species grow naturally in Jambi, Indonesia, i.e. opon (Plectocomiopsis geminiflora (Griff.) Beccari), udang (Korthalsia flagelaris Miquel), getah (Daemonorops micracantha (Griff.) Beccari), duduk (D. didymophylla Beccari), tunggal (Calamus laevigatus Martius), sijau (C. tumidus Furtado), buruk ati (C. insignis Griff. var. longispinosus Dransfield), batu (C. zonatus Beccari), and paku (C. exillis Griff.). The rattan species are classified as lesser known species, which its properties are unknown to rattan supplier and consumers. This paper observes the anatomical properties of nine indigeneous rattan species of Jambi. Anatomical observations were conducted from solid, sectioned and macerated samples. Results show that anatomical properties become a diagnostic characteristic for rattan species identification and specific characteristic has been developed for key species determination. Vascular bundles in the outer part of the stem of opon and udang rattans are yellow-capped. Width and length ratio of vascular bundle in the outer part is more than 1, oval shape was found in sijau rattan, while elongated shape vascular bundle with the ratio less than 1 was found in buruk ati. Fiber bundles separated from vessels are found in central ground parencymatous tissue of rattan tunggal. In the peripheral area, fiber bundle forms one or two lines with no specific pattern found in rattan paku, while fiber bundles in one line with alternate pattern found in rattan duduk. Single resin canals are found both in center part and peripheral area is found in batu rattan and mostly single. Resin canals are found in pair at getah rattan stem. Tentative identification key to rattan species has been developed for nine species investigated, then the key should be developed for further genera identification among rattan species in Indonesia.